Operator for Construction of Archimedian Triangular Norms (Моделювання, керування та інформаційні технології, 2019)
Triangular norms and associative functions arebase of connectives in fuzzy logic and fuzzy systems. Newconnective operator that can generate different classes of fuzzyconnectives is proposed. It is proved that this operator satisfiesthe requirements of such axioms as commutativity, associativity,monotonicity and boundary conditions. It is parameterized andtherefore new triangular norms are obtained. Constructedparameterized triangular norms are of a strict and Archimediantype.